Software Engineering Perspective of Reconfigurable Hardware Programming - Khazem, Raafah; Sulaiman, Samer Mumtaz (Latakia University Journal -Engineering Sciences Series, 2019)
Developing a software system is a task that has been done by several companies over a long time, Projects differ in their nature as some require real-time processing, or might have hardware involved in them, so these factors might affect the overall development process and might even have a bad effect if not handled properly. Reconfigurable hardware-based projects are a special case of software projects, which was being concentrated on a lot in Syria in the recent years. The recommendations that were presented to software production companies made a slight improvement to the overall performance of the development team as all these recommendations revolve around the fact that all parts of the team whether they were analysts or programmers must get involved with the hardware being used in order to better understand how to plan and expect this hardware to operate. تقوم العديد من الشركات بتطوير النظم البرمجية بشكل دوري منذ فترة زمنية طويلة، تختلف المشاريع بطبيعتها حيث أنَّ بعض هذه المشاريع قد يتطلب معالجة في الزمن الحقيقي (Real-time) أو قد تتضمن عتادًا كأحد مكونات النظام. فهذه العوامل وغيرها قد تؤثر بعملية التطوير الكلية ويمكن أن يكون لها آثار سلبيّة إذ تمّ التعامل معها بشكل غير مناسب. تعتبر المشاريع البرمجية المعتمدة على العتاد القابل لإعادة الضبط (Reconfigurable hardware-based projects) حالة خاصة من المشاريع البرمجية والتي لقيت اهتمامًا كبيراً في سوريا في السنين الأخيرة. لقد ساهمت التوصيات المقدمة للشركات المنتجة للبرمجيات في تحسين الأداء الكلي لفريق التطوير حيث أنَّ كل هذه التوصيات تدور حول أهمية انخراط فريق التطوير كاملًا من محللين ومبرمجين في العتاد مما يسهم في تحقيق فهم أفضل للمشروع وبالتالي معرفة كيفية التخطيط وما يمكن أن نتوقعه من العتاد بشكل صحيح.